Cytosine modifications exhibit circadian oscillations that are involved in epigenetic diversity and aging - Oh, Gabriel; Ebrahimi, Sasha; Carlucci, Matthew; Zhang, Aiping; Nair, Akhil; Groot, Daniel E.; Labrie, Viviane; Jia, Peixin; Oh, Edward S.; Jeremian, Richie H.; Susic, Miki; Shrestha, Tenjin C.; et al. (Nature communications, 2018)
Circadian rhythmicity governs a remarkable array of fundamental biological functions and is mediated by cyclical transcriptomic and proteomic activities. Epigenetic factors are also involved in this circadian machinery; however, despite extensive efforts, detection and characterization of circadian cytosine modifications at the nucleotide level have remained elusive. In this study, we report that a large proportion of epigenetically variable cytosines show a circadian pattern in their modification status in mice. Importantly, the cytosines with circadian epigenetic oscillations significantly overlap with the cytosines exhibiting age-related changes in their modification status. Our findings suggest that evolutionary advantageous processes such as circadian rhythmicity can also contribute to an organism’s deterioration. While epigenetic factors have been implicated in the circadian rhythm, the detection of circadian cytosine modifications has remained elusive. Here the authors identify a large number of epigenetically variable cytosines that show circadian oscillations in their modification status in mice.